Project Hail Mary [large type] : a novel - Weir, Andy (Random House Large Print, 2021)
The sole survivor on a desperate, last-chance mission to save both humanity and Earth, Ryland Grace is hurtled into the depths of space when he must conquer an extinction-level threat to our species.